“Circuito abierto” en EspacioCal: aproximaciones y efectos de una exposición de mujeres en 1983 - Campillay Covarrubias, Catherina; Flores Leiva, Mariairis (Revista de Teoría del Arte, 2022)
This paper aims to analyze the exhibition “Circuito abierto”, held in 1983 in EspacioCal, and in which participated the Chilean artists Patricia del Canto (b. 1948), Lea Kleiner (b. 1929), Mireya Larenas (b. 1932), Ma- ria de la Luz Torres (b. 1943) and Gilda Hernandez (b. 1935). For this, we will focus on the article “Being a Woman” by Marianne Carey, which was published about the exhibition in Paula magazine. Establishing as a trigger the proposal that Linda Nochlin articulated fifty years ago, the article delves into an unconventional exhibition model and how it allows us to reflect on the idea of the “women’s exhibitions”, its meanings in its historical moment and how the sign of woman is configured in the context of the field of visual arts of the time.